High moisture corn ensiled with urea for cattle finishing rations - Young, B.; Smith, R.; Bolsen, K.; Ilg, H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Dry rolled corn, ensiled high moisture corn, and high moisture corn that was rolled and ensiled with urea or left whole and ensiled with urea were compared in two cattle trials. Dry corn gave the poorest cattle performance; rolled, ensiled high moisture corn gave the best. When corn was left whole, adding urea prior to ensiling increased dry matter losses in the silo and produced a butyric acid fermentation. Urea increased the bunk life of the ensiled high moisture corn.
Keywords: Beef; Corn; Silo; Urea; Finishing cattle; Rations